Assist towards success: a project for inclusion (through) digital - Barbara Bruschi; Paola Ricchiardi; Emanuela M. Torre (Firenze University Press, 2022)
Numerous studies attest, in a convergent manner in different countries, the effects on minors of the pandemic period, especially on those in educational poverty. This condition requires articulated projects, centered on emerging needs, based on research and supported by a network on the territory. The Assist towards success program was created to include lower secondary school students, for whom the pandemic has meant a significant loss of learning opportunities. The interventions envisaged a targeted use of technologies and the involvement of trainees in Education, trained in remote cognitive mediation strategies. This choice also promoted in future professionals specific skills in school support; transversal skills and responsibility towards the needs of the territory. The implementation strategies of the Assist program and its effectiveness outcomes can constitute a model for future planning, within an educational world that has been profoundly renewed by the health emergency.   Un Assist verso il successo: un progetto per l'inclusione (attraverso il) digitale. Numerosi studi attestano, in maniera convergente in diversi Paesi, gli effetti del prolungarsi della pandemia sui minori, specie se in condizione di povertà educativa. Tale condizione necessita di progetti articolati, centrati sui bisogni emergenti, fondati sulla ricerca e supportati da una rete sul territorio. Il programma Un Assist verso il successo è nato per garantire l'inclusione degli studenti della scuola secondaria di I grado, per i quali la pandemia ha significato la perdita importante di opportunità di apprendimento. Gli interventi sperimentali hanno previsto un uso mirato delle tecnologie e il coinvolgimento di tirocinanti di Scienze dell'educazione, formati sulle strategie di mediazione cognitiva a distanza. Tale scelta ha anche promosso nei futuri professionisti competenze specifiche nel sostegno scolastico; abilità trasversali e responsabilizzazione rispetto ai bisogni del territorio. Le strategie di realizzazione del programma Assist e gli esiti di efficacia dello stesso possono costituire un modello per progettazioni future, in un mondo educativo profondamente rinnovato dall'emergenza sanitaria.